A cross-sectional analysis of diagnosis and management of chronic obstructive pulmonary disease in people living with HIV: Opportunities for improvement. Issue 37 (17th September 2021) - Zifodya, Jerry S.; Triplette, Matthew; Shahrir, Shahida; Attia, Engi F.; Akgun, Kathleen M.; Soo Hoo, Grant W.; Rodriguez-Barradas, Maria C.; Wongtrakool, Cherry; Huang, Laurence; Crothers, Kristina
Abstract : Abstract: Chronic obstructive pulmonary disease (COPD) is common in people living with HIV (PLWH). We sought to evaluate the appropriateness of COPD diagnosis and management in PLWH, comparing results to HIV-uninfected persons. We conducted a cross-sectional analysis of Veterans enrolled in the Examinations of HIV-Associated Lung Emphysema study, in which all participants underwent spirometry at enrollment and reported respiratory symptoms on self-completed surveys. Primary outcomes were misdiagnosis and under-diagnosis of COPD, and the frequency and appropriateness of inhaler prescriptions. Misdiagnosis was defined as having an International Classification of Diseases (ICD)-9 diagnosis of COPD without spirometric airflow limitation (post-bronchodilator forced expiratory volume in 1-second [FEV1]/Forced vital capacity [FVC] < 0.7). Under-diagnosis was defined as having spirometry-defined COPD without a prior ICD-9 diagnosis. The analytic cohort included 183 PLWH and 152 HIV-uninfected participants. Of 25 PLWH with an ICD-9 diagnosis of COPD, 56% were misdiagnosed. Of 38 PLWH with spirometry-defined COPD, 71% were under-diagnosed. In PLWH under-diagnosed with COPD, 85% reported respiratory symptoms. Among PLWH with an ICD-9 COPD diagnosis as well as in those with spirometry-defined COPD, long-acting inhalers, particularly long-acting bronchodilators (both beta-agonists and muscarinic antagonists) were prescribed infrequently even in symptomatic individuals. Inhaled corticosteroids were the most frequently prescribed long-acting inhaler in PLWH (28%). Results were overall similar amongst the HIV-uninfected. COPD was frequently misdiagnosed and under-diagnosed in PLWH, similar to uninfected-veterans. Among PLWH with COPD and a likely indication for therapy, long-acting inhalers were prescribed infrequently, particularly guideline-concordant, first-line long-acting bronchodilators. Although not a first-line controller therapy for COPD, inhaled corticosteroids were prescribed more often.